The Relationship Between Social Media Access and Student Achievement Motivation - Nurhikmah, Nazilah; Martono, Nanang; Puspitasari, Elis; Kurniawan, Agung; Prasetyoningsih, Tri Wahyu Setiawan (The Journal of Society and Media, 2024)
The development of the globalization era has caused many changes, one of which is the increasingly sophisticated technology. Social media is a phenomenon as a result of technological advancement. It can be accessed by all groups, including teenagers. The growing level of social media use among teenagers can affect various aspects of their lives, including academic and non-academic achievement motivation. This study aims to find out the relationship between social media access and student achievement motivation. This study uses a quantitative method in the form of a survey. Data was obtained through questionnaires and interviews. The data analysis technique uses Kendall’s correlation. The results of the study show a positive relationship between social media access and student achievement motivation. The p value or significance of 0.002 indicates that there is a substance relationship between the two variables because the p-value is 0.002 <α 0.05 at a significance level of 99% (0.01). Social media is a factor that influences motivation for student achievement. This can happen because of imitation behavior towards positive content on the accounts they follow regarding achievements. Social media helps students to get learning materials and makes it easier to get information about competitions.